2014
DOI: 10.5588/ijtld.14.0297
|View full text |Cite
|
Sign up to set email alerts
|

False-positive rifampicin resistance on Xpert<SUP>®</SUP> MTB/RIF caused by a silent mutation in the <I>rpo</I>B gene

Abstract: The Xpert® MTB/RIF assay detects the presence of Mycobacterium tuberculosis and its resistance to rifampicin (RMP) directly in sputum samples. Discrepant results were observed in a case of smear-positive pulmonary tuberculosis that was Xpert-resistant but phenotypically susceptible to RMP. Complementary investigations (repeat Xpert, Genotype®MTBDRplus assay and sequencing of the rpoB gene) revealed the presence of a silent mutation in the rpoB gene, leading to the conclusion of a false-positive Xpert result. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…The prevalence of these types of mutations is unknown and warrants a larger survey. However, our data are consistent with recent reports (6,9) and support the recommendation to confirm Xpert RIF r results with both molecular methods that allow for the specific DNA sequence and culture-based DST. DNA sequencing results are useful for interpretation of results from Xpert and for resolving potential discordant results between the Xpert and culture-based methods.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of these types of mutations is unknown and warrants a larger survey. However, our data are consistent with recent reports (6,9) and support the recommendation to confirm Xpert RIF r results with both molecular methods that allow for the specific DNA sequence and culture-based DST. DNA sequencing results are useful for interpretation of results from Xpert and for resolving potential discordant results between the Xpert and culture-based methods.…”
supporting
confidence: 82%
“…This assay can be performed on raw or concentrated sputum sediments using the fully automated GeneXpert Instrument and provides rapid results weeks earlier than culture-based methods (8). However, some experts have recommended that RIF r detected by Xpert be confirmed by DNA sequencing due to the potential low positive predictive value for detection of RIF r , attributable to the low prevalence of drug resistance among U.S. TB cases and because the output of Xpert does not provide the specific rpoB mutation detected (i.e., the probes detect the presence of wild-type sequence) (9). Knowing the specific mutation detected is necessary because silent mutations can lead to false resistance by Xpert and "disputed" mutations may lead to discordant culture-based DST results.…”
mentioning
confidence: 99%
“…It is well known that more than 90% of RIF resistance is associated with INH resistance (23); for this reason, RIF resistance is widely used by other commercial tests, such as the GeneXpert MTB/RIF assay, as a surrogate marker for MDR-TB (23). It was shown that a number of false-positive results for RIF resistance were detected with those assays, however, and the consequences were discussed from clinical and public health perspectives (24). In this context, the molecular detection of INH resistance, as with the Anyplex assay, can provide a useful tool for effective identification of MDR-TB strains (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…TB (detecting resistance to RMP only) and the GenoType MTBDRplus (detecting resistance to RMP and INH), as well as the real-time PCR-based automated Xpert MTB/RIF (Xpert) assay (detecting resistance to RMP only) (3,5). However, these tests are not specific, as silent mutations in the rpoB gene occasionally lead to the detection of false-positive RMP resistance (6)(7)(8)(9). The current WHO recommendations are to use the Xpert assay as the initial diagnostic test and start treatment for MDR-TB if an RMP resistance result is expected, or, if unexpected, to repeat Xpert assay testing on another sputum sample, particularly in settings in which the prevalence of RMP-resistant TB is Ͻ15% (10).…”
mentioning
confidence: 99%
“…The Xpert assay result represents real false-positive RMP resistance, since silent mutations do not change the properties of encoded proteins, and this reinforces the recommendations of the WHO to perform a confirmatory DST by phenotypic or other genotypic methods and to resolve any discordant RMP susceptibility results by sequencing of the rpoB gene (10). Silent mutations in the rpoB gene have been reported at codon Thr508 in Haitian isolates (9), Gln510 in New Zealand isolates (7), Leu511 and Gln513 in South Korean isolates (21), Phe514 in Spanish and American isolates (6,22), Thr525 in Chinese isolates (23), Ala532 in Indian isolates (24), and Leu533 in Indian and Belgian isolates (8,24). The growing body of literature on silent mutations within the RRDR of the rpoB gene is alarming, since the Xpert assay was designed for the rapid diagnosis of MDR-TB for effective management of such patients, but it may actually result in overdiagnosis of MDR-TB in resource-poor settings due to limited access to confirmatory DST by phenotypic methods or rpoB sequencing.…”
mentioning
confidence: 99%